Efficacy of motivational-interviewing and guided opioid tapering support for patients undergoing orthopedic surgery (MI-Opioid Taper): A prospective, assessor-blind, randomized controlled pilot trial. (November 2020) - Hah, Jennifer M.; Trafton, Jodie A.; Narasimhan, Balasubramanian; Krishnamurthy, Partha; Hilmoe, Heather; Sharifzadeh, Yasamin; Huddleston, James I.; Amanatullah, Derek; Maloney, William J.; Goodman, Stuart; Carroll, Ian; Mackey, Sean C.
Abstract: Background: Postoperative opioid use can lead to chronic use and misuse. Few studies have examined effective approaches to taper postoperative opioid use while maintaining adequate analgesia. Methods: This randomized, assessor-blinded, pilot trial of postoperative motivational interviewing and guided opioid tapering support (MI-Opioid Taper) added to usual care (UC) enrolled patients undergoing total hip or knee arthroplasty at a single U.S. academic medical center. MI-Opioid Taper involved weekly (to seven weeks) and monthly (to one year) phone calls until patient-reported opioid cessation. Opioid tapering involved 25% weekly dose reductions. The primary feasibility outcome was study completion in the group to which participants were randomized. The primary efficacy outcome, time to baseline opioid use, was the first of five consecutive days of return to baseline preoperative dose. Intention-to-treat analysis with Cox proportional hazards regression was adjusted for operation. ClinicalTrials.gov registration: NCT02070003. Findings: From November 26, 2014, to April 27, 2018, 209 patients were screened, and 104 patients were assigned to receive MI-Opioid Taper (49 patients) or UC only (55 patients). Study completion after randomization was similar between groups (96.4%, 53 patients receiving UC, 91.8%, 45 patients receiving MI-Opioid Taper). Patients receiving MI-Opioid Taper had a 62% increase in the rate of return to baseline opioid use after surgery (HR 1.62; 95%CI 1.06–2.46; p = 003). No trial-related adverse events occurred. Interpretation: In patients undergoing total joint arthroplasty, MI-Opioid Taper is feasible and future research is needed to establish the efficacy of MI-Opioid Taper to promote postoperative opioid cessation. Funding: National Institute on Drug Abuse